Association Between Dyslipidemia and Dry Eye Syndrome Among the Korean Middle-Aged Population. Issue 2 (February 2020) - Choi, Hye Rin; Lee, Jung Hyun; Lee, Hyung Keun; Song, Jong Suk; Kim, Hyeon Chang
Abstract : Purpose: Dry eye syndrome (DES) is a common eye disease caused by tear deficiency or excessive tear evaporation. Because the tear film layers play a major role in the pathogenesis of the evaporative dry eye, some previous articles have suggested the possible mechanism of dyslipidemia and DES. However, the previous results were inconsistent and few studies were conducted to find the independent relationship between dyslipidemia and DES. Therefore, we investigated the association of dyslipidemia with DES in middle-aged Korean adults. Methods: This study was conducted on 2272 participants (854 men and 1418 women) enrolled in the Study Group for Environmental Eye Disease (2013–2017) after excluding people who have taken lipid-lowering medication. Participants with total cholesterol ≥240 mg/dL or high-density lipoprotein cholesterol <40 mg/dL or low-density lipoprotein cholesterol ≥160 mg/dL or triglycerides ≥200 mg/dL are defined as having dyslipidemia. Using the ocular surface disease index, we measured the DES severity and defined DES as an ocular surface disease index score ≥13. Results: Men with dyslipidemia had an odds ratio of 1.29 (95% confidence interval, 0.97–1.71) for DES in an unadjusted model compared with those without DES. After adjusting for age, body mass index, hypertension, diabetes, occupations, smoking and drinking status, exercise, contact lens use, computer use, study cohorts, and calendar year of examinations, the adjusted odds ratio for DES was 1.40 (1.03–1.90) in men. However, there was no significant association between dyslipidemia and DES in women, even after stratifying by menopausal status. Conclusions: Our findings suggest that dyslipidemia may be associated with the prevalence of DES in Korean men, but not in women. Abstract : Supplemental Digital Content is Available in the Text.